Kajian Ayat-Ayat Ekonomi dalam Al-Qur'an: Panduan Perdagangan Islami Berdasarkan Tafsir Tematik - Ayu, Kemala; Jamal, H. Khairunnas (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study discusses the economic verses in the Qur'an as a guide to Islamic trade, with a thematic interpretation approach. The scope of the study includes the principles of trade such as justice, honesty, prohibition of usury, and recommendations for halal transactions. The aim is to formulate the concept of Islamic trade based on the values ​​of the Qur'an that are relevant to modern economic practices. The study uses a qualitative method with thematic analysis of the verses of the Qur'an, supported by classical and contemporary interpretations. The results show that the Qur'an provides holistic guidelines in trade, emphasizing ethics, balance, and social responsibility. The conclusion of the study confirms that the application of Islamic economic values ​​can create a fair and sustainable trade system